Preparation, characterization, and optimization of altretamine-loaded solid lipid nanoparticles using Box-Behnken design and response surface methodology. (17th February 2016) - Gidwani, Bina; Vyas, Amber
Abstract : The objective of the present study was to prepare solid lipid nanoparticles (SLNs) of altretamine (ALT) by the hot homogenization and ultrasonication method. The study was conducted using the Box-Behnken design (BBD), with a 3 3 design and a total of 17 experimental runs, performed in combination with response surface methodology (RSM). The SLNs were evaluated for mean particle size, entrapment efficiency, and drug-loading. The optimized formulation, with a desirability factor of 0.92, was selected and characterized. In vitro release studies showed a biphasic release pattern from the SLNs for up to 24 h. The results of % EE (93.21 ± 1.5), %DL (1.15 ± 0.6), and mean diameter of (100.6 ± 2.1) nm, were very close to the predicted values.